A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 5 years ago
Solve (xy)dx+xdy=0
anonymous
 5 years ago
Solve (xy)dx+xdy=0

This Question is Closed

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0y=ux dy=udu+xdx dx=1 so dy=udu+xdx I try to substitute. Is it ok if I leave out the dx?

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0y=ux dy=udu+xdx dx=1 so dy=udu+x

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0You have to integrate no?

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0What topic of the course is this from?

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0homogeneous substitution

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0(xux)dx+x(udu+x)=0 xdxuxdx+xudu+x^2=0 work correct so far?

myininaya
 5 years ago
Best ResponseYou've already chosen the best response.1where the C above is a constant

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0tell me myininaya if my work is correct

myininaya
 5 years ago
Best ResponseYou've already chosen the best response.1i dont know the way you are doing it im sorry

myininaya
 5 years ago
Best ResponseYou've already chosen the best response.1but i posted above how i got my answer if that helps

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0please visit site orlandoicc.org

anonymous
 5 years ago
Best ResponseYou've already chosen the best response.0why do you multiply by v?

myininaya
 5 years ago
Best ResponseYou've already chosen the best response.1i multiply by v (i choose this v such that we have vy'+v'y=(yv)')

myininaya
 5 years ago
Best ResponseYou've already chosen the best response.1if we can write the differential equation in this form y'+p(x)y=q(x) then we can multiply by v such that we have vy'+vpy=vq but we want this v so that v'=vp so we can write the next step as (vy)'=vq

myininaya
 5 years ago
Best ResponseYou've already chosen the best response.1v'=pv dv/dx=pv 1/v dv=p dx lnv=p dx so we have v=e^(int p dx)

myininaya
 5 years ago
Best ResponseYou've already chosen the best response.1so we multiply whatever that v is on both sides of the equation then we can write the (vy)'=vq integrate both sides vy=int(vq)+C solve for y y=1/v*int(vq) +C/v
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.